D17 Effects of the huntingtin gene (HTT) on brain development. (13th September 2016) - Nopoulos, Peggy; Lee, Jessica; Epping, Eric; Mathews, Kathy; Magnotta, Vincent; Dawson, Jeffrey
Abstract : Background: The Huntingtin gene (HTT) has a unique feature of trinucleotide repeats ranging from 10–35 in healthy people, and when expanded beyond 40, causes disease. It has been shown that HTT is vital to brain development in animal models, however this has not been studied in humans. Moreover, evidence suggests that triplet repeat genes may have been vital in the evolution of the human brain. Aim: To evaluate brain structure and function in a large sample of children ages 6–18 and with CAG repeat lengths from 15–59. Methods: The University of Iowa Kids-HD program enrols children 8–18 years of age who are 1) healthy developing children with no family history of HD (N = 138), and 2) those who have a parent or grandparent with HD (n = 147). DNA is obtained for CAG repeat length. Each child undergoes an MRI scan and cognitive testing. Children are followed up for repeat testing. For this analysis, there were a total of 394 observations. Mixed models accounting for repeat visits evaluate the effects of CAG repeat length on cognitive and brain measures, controlling for age, sex, and parental social class. Interactions with sex and non-linear relationships were evaluated Results: General measures of Intracranial Volume (ICV) and Intelligence Quotient (IQ) showed significant non-linear relationship with CAG length in which greater repeats lengths were associated with larger ICV and higher IQ until a peak at roughly 41 repeats. Above the peak, increasing repeat lengths were associated with lower ICV and lower IQ. Other brain measures showed sex-specific findings with repeat lengths affecting the striatum and cerebellum in males, and the cortex and thalamus in females. Conclusion: HTT may confer an advantage or a disadvantage depending upon the repeat length, playing a key role in the evolution of a superior human brain, or causing a uniquely human brain disease.